GREEN FOOD PRODUCTS BUYING BEHAVIOUR AMONG MILLENNIALS IN MALAYSIA - Norazlina Rahmat; Anis Farzana Salkhairulizam; Nur Nabihah Rosman; Norzaidah Ngali (International Journal of Accounting, Finance and Business, 2023)
The Malaysian millennial community's interest in the perceived green value of products has risen after realising unhealthy eating and lifestyle have directed consumers to choose green consumption. By applying the theory of planned behaviour (TPB), this study examines the buying behaviour of green food products among millennials in Malaysia. A survey tool was used to obtain data from Malaysian millennials aged 26 to 41. Three hundred eighty-five (385) responses were gathered, and SPSS was used to analyse them. The findings indicated that several factors influence millennial consumers in Malaysia to initiate the buying behaviour of green products, including environmental concern, green products awareness, government support, perceived ecological value, and community green practice. Finally, this study aims to provide insight into consumers in Malaysia. The findings will allow various parties to develop the best strategy for influencing consumers' views toward eating more sustainably green food.